Sensitization and promotion of information literacy on covid-19 pandemic by librarians in public university libraries in south-western Nigeria (2021)
The global spread of coronavirus and the associated lockdown by various countries, communities and organizations is worrisome. However, literature has revealed that one of the biggest roles librarians can to play in the national response to the pandemic is that of information literacy specialist. This study, therefore, evaluated sensitization and promotion of information literacy on COVID-19 pandemic by librarians in Public University Libraries in South-Western Nigeria. The descriptive survey research design was used for the study. The data for the study was collected from librarians in Public University Libraries in South-Western Nigeria. A total of 315 librarians participated in the study through an online questionnaire due to the COVID-19 pandemic while 233 (74.0%) returned copies of filled questionnaire by the respondents was analysed. Frequency counts, percentages and mean were used to analyse the data collected. Librarians sensitized their communities through various ways on preventive COVID-19 information and used mobile phones and social media very effectively in disseminating preventive COVID-19 information. A significant relationship existed between sensitization and promotion of information literacy on COVID-19 pandemic by librarians. However, librarians were confronted with many challenges in promoting preventive COVID-19 information. It is therefore, recommended that librarians and other information stakeholders should put more efforts on sensitizing their communities about this COVID-19 pandemic, so as to reduce the high level of ignorance about the pandemic in the communities.